Extended Exponential and Extorial Type Solutions of Differential and Difference Equations - Sathinathan, T.; Jaraldpushparaj, S.; Xavier, G. Britto Antony (Research and Applications Towards Mathematics and Computer Science Vol. 1, 2023)
This chapter introduces generalized exponential and extorial functions arrived from exponential and extorial functions. These two types of functions are special types of continuous and discrete hyper geometric functions. These functions are applied to arrive find solutions of higher order differential and difference equations. The results are supported by relevant instances.